Keabsahan Smart Contract Dengan Teknologi Blockchain Menurut Kitab Undang-Undang Hukum Perdata - Korintus Wilson Horas Hutapea; Adi Sulistiyono (Aliansi: Jurnal Hukum, Pendidikan dan Sosial Humaniora, 2024)
This article aims to find out the validity of the Civil Code smart contact. It is hoped that the results of this research can be used by parties, especially people who have started carrying out transaction and contract activities using blockchain technology in the form of smart contracts. This research method uses normative law, the use of legal materials includes primary and secondary legal materials, through data collection techniques in the form of literature studies. A conceptual approach and a statutory approach were used in this research. The data analysis technique used is a deductive data analysis technique using the syllogism method. The validity of an agreement is assessed based on an understanding of article 1313 and the main elements of the validity of an agreement based on article 1320 along with the principle of freedom of contract in article 1338 of the Civil Code. It is necessary to understand that smart contracts are required to fulfill the terms of the agreement in their implementation